Exploração madeireira e trabalho análogo ao de escravo no Estado do Pará: o caso do Arquipélago do Marajó - RESQUE, Samir Pinto (Universidade Federal do Pará, 2014)
Slave labor opened during the colonization of Brazil, is still present today. Even in the twenty-first century, it is commonplace knowledge of news and evidence of the incidence of exploitation of workers in conditions analogous to slavery. The new panorama of slave labor brings new causes, different bondages and the most cruel forms of exploitation of human beings. In the case of Amazon, research, data, and studies have shown that in the region linked to deforestation activities are directly related to the incidence of submitting workers to conditions analogous to slavery. Despite the government announced emergency measures to combat deforestation, such measures have been inefficient to reverse this historical trend. In this context, the State of Pará is not oblivious to this reality, presenting itself as an area of serious conflict, not only by land issues and predatory and illegal logging, as well as by the high rates of deforestation and serious violations human rights, factors that have effects even more worrying in areas difficult to access as the Archipelago Marajó. The scope of this study is to analyze the relationship between labor analogous to slavery with the dynamics of deforestation in the Amazon, especially with a case study that relates to logging and cases of labor analogous to slavery in the territory of the Archipelago Marajó.